The beneficial effects of acute strength training on sway activity and sway regularity in healthy older men: Evidence from a posturography study. (1st April 2021) - Drozdova-Statkevičienė, Margarita; Česnaitienė, Vida Janina; Levin, Oron; Pauwels, Lisa; Pukėnas, Kazimieras; Helsen, Werner F.; Staes, Filip; Masiulis, Nerijus
Highlights: Effects of acute strength training on balance control were examined in older adults. Sway activity and wavelet entropy of the CoP trajectory (WEcop) were estimated. WEcop was used to index the amount of attention invested in the postural task. Intervention reduced sway activity and increased attentional regulation of balance​. Abstract: The effects of acute strength training on balance control were studied in healthy older human men (age-range 60–77y). Participants performed the Tandem Romberg Stance while completing an attention demanding cognitive task (Mathematical Counting) before and after a single acute strength training session applied to the lower limb musculature (experimental group; n = 19) or no intervention (control group; n = 18). Balance stability and the automaticity of balance control were estimated through the calculation of the center-of-pressure (CoP) velocity (Vcop) and the statistical regularity (wavelet entropy) of the CoP trajectory (WEcop), respectively. Training included 3 sets of 3 repetitions of barbell squats using Smith Machine, ranging from 90 % of one repetition maximum (1RM) to 100 % 1RM with 3 min rest between repetitions and 5 min rest between sets. Vcop and WEcop decreased after training (all time main effects, p ≤ 0.028) but group time interactions were not significant (all, p ≥ 0.056). Exploratory analyses revealed that participants in the experimental group showed a significant decrease of Vcop and WEcop in the mediolateral (ML) directions from pre to post [ML Vcop: 15.4 %; Bonferroni-corrected p = 0.048); ML WEcop: 10.5 %; Bonferroni-corrected p = 0.016]. A trend towards a decrease in Vcop and WEcop was also observed in controls, with more prominent gains in the anteroposterior than in the ML direction (Bonferroni-corrected p > 0.2). Overall, findings suggest that acute strength training may improve attentional control of balance along the narrow dimension of the support. Further studies are warranted to examine the specific mechanisms underlying these findings.